“Resilient” Vs “Compassionate" Europe: The resilience discourses and their ethical implications in the EU policy environment. - Kyprianidou, Efi; Christidis, Yiannis (My University, 2021)
Resilience is present in everyday life and discussions; references to a system's ability to withstand external pressures and return to normal after a period of crisis appear in the mass media, in political campaigns and in a wide range of academic studies. Resilience is an attractive and "positively charged” notion, replacing negatively charged concepts such as vulnerability or fragility. Resilience is established as a regulatory ideal, both in the context of social and techno-economic systems, and for the individual, who has to be able to recover without delay, reinvent oneself, regain one’s own strengths and skills, and overcome calamities, hardships, or losses. However, the emphasis on resilience as "the set of predispositions, traits and emotions" that help individuals survive has been criticized, as it seems to make the individual solely responsible for their own well-being, ignoring the role of adverse social conditions (poverty, racism, lack of access to resources or education). Furthermore, many point out that, although “resilience” is a central term in the academic literature, the lack of a commonly accepted definition and critical examination of the theoretical framework serves the neoliberal policy agenda. This paper takes these prominent discourses of resilience in the EU and subjects them to critical examination. It attempts to question the dominance of resilience and instead argues for the advancement of a rhetoric of compassion, that acknowledges the importance of compassion as both a political emotion and virtue.
Keywords: Resilience; Dominance of resilience